Short Communication: Note on Excoecaria indica (Willd.) Muell.-Arg, 1863 (Euphorbiaceae), from the Andaman and Nicobar Islands, India; a data deficient species - PADISAMY RAGAVAN; K. RAVICHANDRAN; P. M. MOHAN; ALOK SXAENA; R. S. PRASANTH; R. S.C. JAYARAJ; S. SARAVANAN (Biodiversitas Journal of Biological Diversity, 2015)
Ragavan P, Ravichandran K, Mohan PM, Sxaena A, Prasanth RS, Jayaraj RSJ, Saravanan S. 2015. Note on Excoecariaindica (Willd.) Muell.-Arg, 1863 (Euphorbiaceae), from the Andaman and Nicobar Islands, India; a data deficient species. Biodiversitas 16: 22-26. Excoecaria indica (Wild.) Muell.-Arg was recorded from Middle Andaman and Great Nicobar Island representing a newaddition to the mangrove flora of the, Andaman and Nicobar islands. This species is characterized by its thorny trunk, crenulatelanceolateleaves and cherry-sized green fruits containing three seeds. Information about E. indica is inadequate, and it is recognized asdata deficient species. Further studies and conservation measures are imperative for managing the mangrove diversity of the islands withregards to this species.